Prognostic risk algorithm of the development of microecology disorders of mucous in children of industrial r - Y.G. Resnichenko; M.O. Yartzeva (Bukovynian State Medical University, 2013)
Algorithm of prognostic risk of the development of microecology disorders of mucous in children from industrial region is presented in the article. The influence of the early introduction of formula feeding and using of the mixed feeding, the low socio-economical situation of the family, the presence of anemia, food allergy, nervous system disorders during the first year of life, frequent acute respiratory diseases and the using of antibiotics which is leading to dysbiosis manifestation is ascertained.